Long-Term Outcome of Aromatase Inhibitor Therapy With Letrozole in Patients With Advanced Low-Grade Endometrial Stromal Sarcoma. Issue 9 (November 2015) - Yamaguchi, Munekage; Erdenebaatar, Chimeddulam; Saito, Fumitaka; Motohara, Takeshi; Miyahara, Yo; Tashiro, Hironori; Katabuchi, Hidetaka
Abstract : Background: There has been no consensus on the indications for the treatment of advanced low-grade endometrial stromal sarcoma (LGESS), and the possible effects of hormonal treatment including progestins and aromatase inhibitors have been reported. The aim of this study was to investigate the efficacy of aromatase inhibitor therapy with letrozole for patients with residual or recurrent LGESS. Methods: We retrospectively reviewed the clinical response of patients with advanced LGESS who had been treated with letrozole. We also analyzed the adverse effects after the administration of letrozole. The expression levels of estrogen receptor and aromatase in the tumors were immunohistochemically examined. Results: In 5 patients who had been treated for unresectable LGESS lesions after initial or repeat surgical procedures, residual lesions in 3 patients and recurrence lesions in 2 patients were the indications for hormonal therapy with letrozole. The median duration of letrozole exposure at retrospective analysis was 53 (10–96) months. The clinical outcomes were classified as complete response in 2 patients, partial response in 1 patient, and stable disease in 2 patients. Myalgias, hot flashes, and arthralgias were not observed during the follow-up period in any patients. The median serum levels of estradiol were <5.0 (cutoff value, <0.5–11.8) pg/mL. The median age-matched bone mineral densities were 92% (79%–123%). The LGESS tissues in all 5 patients were positive for estrogen receptor and aromatase expression. Conclusions: Letrozole as well as progestins could be the first choice of treatment for patients with recurrent or residual LGESS, which is difficult to resect surgically because of its efficacy and minimal adverse effects.